2023
DOI: 10.3389/fonc.2023.1129629
|View full text |Cite
|
Sign up to set email alerts
|

The novel EGFR mutations (p.E746_S752delinsI, p.T751_I759delinsG, p.L747_S752delinsAA) in patients with non-small cell lung cancer and the clinical treatment strategy: three case reports

Yamin Meng,
Xiaodong Li,
Lei Zhang
et al.

Abstract: Epidermal growth factor receptor (EGFR) is an established driver gene in non-small cell lung cancer (NSCLC) and the common Exon 19 del mutation (p.E746_A750 del) has exhibited remarkable responses for EGFR tyrosine kinase inhibitors (TKIs). However, there is even less comprehension of the treatment strategy in NSCLC patients harboring uncommon Exon 19 delins mutation. Here, we identified three novel EGFR Exon 19 mutations (p.E746_S752delinsI, p.T751_I759delinsG, p.L747_S752delinsAA), and described the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies have also demonstrated the good safety profile of icotinib, as first-and second-line treatment, as well as in other treatment regimens. Several reports suggest that advanced NSCLC patients with rare EGFR mutations may benefit from icotinib, including P.S.746_S752delinsi [20], double rare EGFR G719D/L861Q mutations, and acquired novel CUX1-MET fusions [21], suggesting that icotinib is a promising EGFR-TKI drug. In one study, a double dose of icotinib in NSCLC patients with EGFRsensitive mutations induced the appearance of T790M in previously T790m-negative patients for subsequent third-generation targeted therapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated the good safety profile of icotinib, as first-and second-line treatment, as well as in other treatment regimens. Several reports suggest that advanced NSCLC patients with rare EGFR mutations may benefit from icotinib, including P.S.746_S752delinsi [20], double rare EGFR G719D/L861Q mutations, and acquired novel CUX1-MET fusions [21], suggesting that icotinib is a promising EGFR-TKI drug. In one study, a double dose of icotinib in NSCLC patients with EGFRsensitive mutations induced the appearance of T790M in previously T790m-negative patients for subsequent third-generation targeted therapy [22].…”
Section: Discussionmentioning
confidence: 99%